Exploring Non-partner Violence in Informal Settlements in Nairobi, Kenya - Winter, Samantha (Journal of interpersonal violence, 2023)
Violence against women is a serious public health and human rights concern and can take many forms. Intimate partner violence (IPV) is the subject of the majority of research focused on violence against women around the world; yet the health consequences of non-partner violence (NPV) can be just as serious. There is a critical gap in literature focused on NPV and the co-occurrence of NPV and IPV in sub-Saharan Africa, particularly in informal settlements. The unique historical, political, social, geo-spatial, physical, and built environment in informal settlements—often characterized as places with high rates of crime and violence—may be important in understanding NPV and co-occurrence of NPV and IPV in these communities, but more research is needed. The purpose of this study was to explore NPV in a large informal settlement in Nairobi, Kenya including its relationship to IPV, correlates, and common perpetrators of NPV in this setting. Data from 552 household-level surveys collected from women in a large informal settlement in Nairobi in 2018 were used in this study. Descriptive statistics and penalized maximum likelihood logistic regressions were used to examine the association between IPV and NPV, correlates, and perpetrators of NPV. Findings showed a strong, positive association between past-year IPV and NPV—highlighting a critical area for future study in IPV, NPV, and poly-victimization research. Results corroborated some findings from existing NPV research, but yielded important new information about correlates and perpetrators of NPV in informal settlements. NPV and poly-victimization have serious health consequences for women in any context, but women in informal settlements also face a number of structural economic, social, political, and environmental challenges that affect their health and wellbeing and may exacerbate the health consequences of violence perpetrated against them. Thus, more research into NPV and poly-victimization in informal settlements is critical.